The Effect of Probiotic Supplementation to The Total Number of Bacteria In Kidney of Nila Fish After Antagonism Test With Aeromonas hydrophila and a typical Aeromonas salmonicida - Ferina Nursanti; Agus lrianto; Hernayanti Hernayanti (Saintek Perikanan : Indonesian Journal of Fisheries Science and Technology, 2006)
This research was aimed to know the effect of A3-51 probiotic supplementation on food to the total number of bacteria in kidney and mortality of nila fish (Oreochromis niloticus). This research was carried out  in two steps, the first was to know the highest immunity level from fish indicated by the increasing number of the macrophage and its phagocytic activity. Meanwhile, the second was to know the immunity level of fish which injected by Aeromonas hydrophila and atypical Aeromonas salmonicida. The experimental method used was Completely Randomized  Design in  3 replicates. The result from the first step showed that the highest  non specific immune system  was found in 21 days treatment.  The second step showed that the highest  total  number  of  bacteria  in  kidney  and  mortality  level  were  20.23 x  10 cells/g  and  46.67% respectively, both was found in B2 treatment.   Key words: probiotic, macrophage, total number of bacteria, mortality